White bone - Pearson, Ridley (Pearson, Ridley. Risk agent novel., 2016)
"When ex-military contractor John Knox receives a text from partner Grace Chu warning that she fears her cover may have been blown while on assignment, he jumps into action. Knox must locate her overseas handlers, convince them of the threat, and then attempt to retrace the well-hidden steps of a woman who had been attempting to determine how one million euros' worth of AIDS vaccine disappeared, all while eluding angry poachers on a parallel trail"--Amazon.com.